Embracing organic farming :A sustainable approach to conquering climate alter - Behera, Supriya; Kar, Ipsita (Indian Farming, 2025)
Global ecosystems and human societies are facing enormous challenges because of climate change. Currently, two of the biggest issues which mankind is facing are averting disastrous climate change and providing food to the World’s expanding population. Even though Indian agriculture has undergone a huge transformation over the years but agriculture is a cause of climate change aswell as a sufferer of it. The best long-term adaptation plan is to switch to organic farming practices. Scientific research has shown that organic farming is a feasible approach which is promising for lowering greenhouse gas (GHG) emissions, improving carbon sequestration, and strengthening ecosystem resilience. Organic agriculture seems to be the most environmentally friendly way tocombat climate change while maintaining food security because it uses low external inputs and high output techniques.